Liberalization, Investment, and Regulation: The Key Factors for the Development of the Electronic Communications Market - Jonida Gjika (European Scientific Journal, ESJ, 2016)
The key factors for the development of the electronic communication market include partial liberalization; full, direct, or indirect investments; and competitive regulation based on transparency and non-discrimination. They are used efficiently in preventing anti-competitive practices through the use of appropriate basic instruments of transparency and non-discrimination. They are used in the proper selection of the “best practice” design and implementation of primary and secondary laws. It is an efficient regulatory framework; it creates adequate space; and they are together considered necessary in influencing the positive development of the electronic communication sector. Proper selection of the "innovative dilemma" that comes from the "technology push" in the sector and harmonization of the time required between the necessary innovation and investment, determines the quality of products/services for the sector tomorrow and its internal markets. At the same time, it determines the eligibility of the request-offer and their quality. The close connection between innovation and entrepreneurship as well as the proper implementation through investments is made tangible and measurable to the quality, price, and their persistence. When these factors are considered in harmony, it will ultimately result in effective competition in the sector. Also, their values are identified by the maximization of social welfare to increased consumer benefits.